A novel strategy to research the mechanism of rutile TiO2 with excellent photocatalytic performance. (27th October 2021) - Han, Bin; Li, Xiangji; Zhang, Zhiming; Wang, Hongyang; Yu, Kaifeng; Liang, Ce
Abstract: This study reported a novel method to obtain rutile TiO2 with excellent photocatalytic activity for degradation of organic dyes. In this study, the concentrated HCl was selected as the inhibitor to make TiO2 precursor hardly hydrolyzed at room temperature. And a certain amount of urea was added, which results in TiO2 precursor hydrolyzed to produce rutile TiO2 due to urea thermally decomposed into alkaline substances to neutralize the concentrated HCl. To further explore the mechanism of excellent photocatalytic performance of rutile TiO2, a series of experiments, characterizations, and DFT computations were carried out. Based on DFT computations and experimental results, it could be concluded that the introduction of surface oxygen vacancies was the main reason for the excellent photocatalytic performance of the samples, and the concentration of surface oxygen vacancies would affect the physical and chemical properties of rutile TiO2 . Meaningfully, this unique and innovative work broke the traditional preconception of rutile TiO2 and provided a theoretical possibility for rutile TiO2 to be applied in other research fields.